Row covers limit pests and disease and increase profit in organic acorn squash - Fiske, Kathleen; Cheng, Nieyan; Kuesel, Ryan; Zhang, Wendong; Bessin, Ricardo; Williams, Mark Alan; Gonthier, David (Frontiers in Sustainable Food Systems, 2024)
Organic cucurbit growers face many challenges to production including insect pests, insect-vectored diseases, and non-vectored diseases. While Organic Material Review Institute (OMRI) -listed pesticides underperform at suppressing pests and diseases, some alternative pest management strategies hold promise, but little research exists on their cost-effectiveness. We compared the efficacy of mesotunnel systems (nylon-mesh netting row covers deployed over bent metal hoops) and OMRI-listed pesticides (fungicides and insecticides) on acorn squash across two years. During the early part of the season, before row covers were removed for pollination, we found 1.7 (2020) and 0.3 (2021) times more cucumber beetles in the uncovered plots compared to the mesotunnels. Powdery mildew incidence was 36% and 25% lower under the mesotunnels compared to the uncovered plots in 2020 and 2021, respectively. Marketable yield of acorn squash was 46-54% higher in the mesotunnels compared to the uncovered treatments. OMRI-listed pesticide treatments reduced powdery mildew incidence compared to untreated control treatments. However, for pest presence, OMRI-listed pesticide treatments did not differ from untreated control treatments in either year, nor did it differ in marketable yield in 2020. Finally, the mesotunnel-only system was 47% more profitable compared to the OMRI-listed pesticide treatment and 47% more profitable compared to the uncovered plots. These results highlight mesotunnels as an economically viable pest management strategy for organic cucurbit growers in the U.S.